Three new phenylspirodrimanes from a conch-derived fungus Stachybotrys sp. NF02434. (12th April 2023) - Xiang, Lang; He, Wen; Yan Ling, Qing; Li, Wei; Yuan Yan, Zhang; Zhang, Bo; Xiang Tan, Ren
Graphical abstract: Abstract: Two new phenylspirodrimanes (1 –2 ) and a new linear biosynthetic precursor (3 ), together with seven known analogues (4 –10 ) were isolated from fermentation broth of a conch-derived fungus Stachybotrys sp. NF02434. The structures of compounds 1 –3 were determined on the basis of comprehensive analyses of HR-ESI-MS and NMR spectroscopic data. Moreover, a plausible biosynthetic pathway for compounds 1 –10 is proposed in this work.